(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article discusses international standards used in teaching and assessing the English language. It focuses on the CEFR framework and international examinations such as IELTS and TOEFL. The article also explains the importance of modern assessment methods in improving the quality of English language education.